MULTI-LEVEL MARKETING AGREEMENT WITH ITS MEMBERS AT PT NATURA PRIMA BEAUTY BASED ON FATWA NO. 75/DSN-MUI/VII/2009 - Nabila Ramadhani; Soraya Devi; Ajidar Matsyah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This article examines the rapid development of modern marketing systems, particularly through Multi-Level Marketing (MLM), in Aceh, a region that implements Islamic law comprehensively. This raises questions about the compliance of MLM practices with the principles of Islamic muamalah, particularly in reference to DSN-MUI Fatwa No. 75/2009 on Sharia Direct Selling (PLBS). This study focuses on two issues: (1) the conformity of MLM agreements applied by PT Natura Prima Beauty with DSN-MUI Fatwa No. 75/2009; and (2) the form of agreements used by the company for its members. Using a qualitative juridical-normative method combined with field research at the Banda Aceh Stockist, the findings indicate that agreements are not established through individual written contracts but are instead regulated by a collective code of ethics binding all members. The code of ethics outlines rights, obligations, and prohibitions, and is considered a valid contract (akad) from a sharia perspective. Bonus mechanisms based on real sales, transparency through IT systems, and upline–downline mentoring ensure fairness and business sustainability. Overall, this practice meets the 12 requirements set by DSN-MUI Fatwa No. 75/2009, although challenges remain in terms of formal regulation in Aceh.